ResCA - 8th Semi-Annual Progress Report - The Nature Conservancy; AgroLAC (2020)
To advance the goals of the Resilient Central America (ResCA) program, we have achieved the following results in the April 2020 to September 2020 semester reporting period. Regarding climate change adaptation, this semester we trained a total of 1141 people; 990 men (86.8%) and 151 women (13.2%). We also strengthened 30 institutions; 1 from the public sector at the national level; 8 from the public sector at subnational level and 21 local organizations. With collaborating institutions and stakeholders, 8 policies were proposed at the sub-national level. We achieved the adoption of 7 policies; 3 at the sub-national level and 4 at the national level. We also achieved the implementation of 6 policies; 5 at the sub-national level and 1 at the national level.